Best Practice for Measuring Permafrost Temperature in Boreholes Based on the Experience in the Swiss Alps - Noetzli, Jeannette; Arenson, Lukas U.; Bast, Alexander; Beutel, Jan; Delaloye, Reynald; Farinotti, Daniel; Gruber, Stephan; Gubler, Hansueli; Haeberli, Wilfried; Hasler, Andreas; Hauck, Christian; Hiller, Martin; et al. (Frontiers in Earth Science, 2021)
Temperature measurements in boreholes are the most common method allowing the quantitative and direct observation of permafrost evolution in the context of climate change. Existing boreholes and monitoring networks often emerged in a scientific context targeting different objectives and with different setups. A standardised, well-planned and robust instrumentation of boreholes for long-term operation is crucial to deliver comparable, high-quality data for scientific analyses and assessments. However, only a limited number of guidelines are available, particularly for mountain regions. In this paper, we discuss challenges and devise best practice recommendations for permafrost temperature measurements at single sites as well as in a network, based on two decades of experience gained in the framework of the Swiss Permafrost Monitoring Network PERMOS. These recommendations apply to permafrost observations in mountain regions, although many aspects also apply to polar lowlands. The main recommendations are 1) to thoroughly consider criteria for site selection based the objective of the measurements as well as on preliminary studies and available data, 2) to define the sampling strategy during planification, 3) to engage experienced drilling teams who can cope with inhomogeneous and potentially unstable subsurface material, 4) to select standardised and robust instrumentation with high accuracy temperature sensors and excellent long-term stability when calibrated at 0 °C, ideally with double sensors at key depths for validation and substitution of questionable data, 5) to apply standardised maintenance procedures allowing maximum comparability and minimum data processing, 6) to implement regular data control procedures, and 7) to ensure remote data access allowing for rapid trouble shooting and timely reporting. Data gaps can be avoided by timely planning of replacement boreholes. Recommendations for standardised procedures regarding data quality documentation, processing and final publication will follow later.